2003
DOI: 10.1021/es034368i
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Fate of Macrolide Antibiotics in Wastewater Treatment Plants and in the Glatt Valley Watershed, Switzerland

Abstract: An analytical method was developed for determining macrolide antibiotics in treated wastewater effluents and in ambient water based on solid-phase extraction and LC/MS analysis as well as on LC/MS/MS for structural confirmation. In wastewater treatment plants (WWTPs) macrolides are only partly eliminated and can therefore reach the aquatic environment. In treated effluents from three WWTPs in Switzerland, clarithromycin, roxithromycin, and erythromycin-H2O, the main degradation product of erythromycin, were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
225
2
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 431 publications
(241 citation statements)
references
References 16 publications
9
225
2
5
Order By: Relevance
“…It is recommended as it was shown that MLs can bind divalent and polyvalent cations although they bind not so strong as TCs or FQs. The extraction was performed with polymeric Oasis HLB columns except one study using LiChrolute RP-18 sorbent [5].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is recommended as it was shown that MLs can bind divalent and polyvalent cations although they bind not so strong as TCs or FQs. The extraction was performed with polymeric Oasis HLB columns except one study using LiChrolute RP-18 sorbent [5].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
“…The washing step was performed with water in three studies. The other study does not report the washing step although WWTPs effluents were analyzed [5]. It can be seen from recovery achieved that washing step was necessary.…”
Section: Macrolide Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations